Analisis Pertumbuhan dan Kandungan Antioksidan Tanaman Bawang Dayak (Aleutherine bulbosa Merr.) dengan Pupuk Terpadu di Lahan Terbatas - Evi Setiawati; Darnawi; Maria Theresia Darini; Ihsan; Ig. S. Sudrajad (J-Plantasimbiosa, 2026)
Dayak onion is a medicinal plant with significant therapeutic properties and has the potential to be cultivated in various regions, including urban areas. Efforts to increase its productivity can be carried out through the application of integrated fertilization technology on limited land. This research aimed to evaluate the impact of combining natural organic fertilizer with synthetic fertilizer on plant growth, yield, and antioxidant content of the medicinal plant dayak onion (Aleutherine bulbosa Merr.). The activity was carried out in a yard in Krikilan Hamlet, Tegaltirto Village, Berbah District, Sleman Regency, D.I. Yogyakarta in February to July 2024, at an altitude of approximately 114 m above sea level, with an average rainfall of 16.2 mm per year and a temperature range of 28 to 39 °C. The research method employed was a field experiment arranged in a factorial Completely Randomized Design {(3x4) X 3 = 36 units}, where each treatment unit consisted of 8 polybags of plants, with 4 plants designated as sample plants. The first factor was the source of natural organic fertilizer, consisting of 3 levels: cow manure (P1), goat manure (P2), and household waste compost (P3). The second factor was the dose of urea fertilizer, consisting of 4 levels: 0 (N0), 4 (N1), 6 (N2), and 8 (N3) g/polybag. Observations were conducted destructively at 4 and 6 months, including measurements of leaf area, net assimilation rate, bulb weight, relative growth rate, plant index, vitamin C content, and carotene content. The results of the study showed an interaction between the sources of organic fertilizer and the doses of urea fertilizer on all observation variables. The weight of the dayak onion bulbs at 4 and 6 months was high, with a significant vitamin C content. The growth analysis suggested using cow or goat manure or compost with a urea fertilizer dose of 4 g/plant, while a high carotene content was also obtained from various organic sources, although a urea dose of 8 g/plant was needed